Accountability in Managing Business Funds through Budgeting to SME's - I Gusti Ketut Agung Ulupui; Siti Fatimah Zahra; Dwi Handarini (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2020)
The classic problem that is still inherent in SME’s activities is the lack ofcapital. This is also felt by SMEs in the Tarumajaya sub-district, North Bekasi,West Java. So, there is a need for appropriate fund management andbudgeting. Therefore, this activity aims to provide workshops related toaccountability, good procedures for managing business funds, as well asproviding budgeting practices for SMEs. The method of implementing PKMactivities consists of 3 stages, namely: planning, implementation, andevaluation. The workshop was held in the Hall of TPI PALIJAYA Segara JayaVillage and was attended by 54 business people with different business objects.The material was delivered in the form of theory and practice, followed by adiscussion and question and answer session with the participants. Based on theresults of the questionnaire survey, it was found that before this training, only23% of the trainees stated that they had planned a business activity budget.Only 17% stated that they used to record transactions related to their businessactivities routinely. After this training, the participants increasingly understoodthe importance of budgeting in business. Thus, an assessment of 90% ofparticipants stated that the business budget was an important matter. As for theparticipant's assessment of the whole set of activities, 83% stated that thematerial presented by the service team was important, and 77% stated it wasuseful. As many as 73% of participants stated that the material had beendelivered by the service team clearly, and 87% of participants expressedsatisfaction with the community service activities carried out by the communityservice team from FE UNJ.